2012
DOI: 10.1002/jbm.b.32509
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bone marrow aspirate, bone graft, and collagen composites on fixation of titanium implants

Abstract: Autograft and allograft have similar effect on fixation of bone implants. HA/Collagen composite with or without BMA has no effect on the early fixation of bone implants in this sheep model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The size of implant was designed according to the anatomy at the implantation site of sheep distal femur trabecular bone. Four titanium implants with 2 mm concentric gaps were inserted extra‐articularly into the medial and lateral femoral condyles . The gaps were filled with one of the four materials: allograft as control, ABM/P‐15, HA/βTCP‐PDLLA, or ABM/P‐15+HA/βTCP‐PDLLA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of implant was designed according to the anatomy at the implantation site of sheep distal femur trabecular bone. Four titanium implants with 2 mm concentric gaps were inserted extra‐articularly into the medial and lateral femoral condyles . The gaps were filled with one of the four materials: allograft as control, ABM/P‐15, HA/βTCP‐PDLLA, or ABM/P‐15+HA/βTCP‐PDLLA.…”
Section: Methodsmentioning
confidence: 99%
“…The wounds were closed with sutures in three layers. Three times daily 2.0 mL buprenorphine (0.03 mg/mL, Temgesic, Schering‐Plough, Denmark ) and once daily 9.0 mL ampicillin (250 mg/mL, Ampivet Vet, Boehringer Ingelheim, Denmark ) were given postoperatively for one week …”
Section: Methodsmentioning
confidence: 99%
“…The gap was filled with the hydroxyapatite/collagen composites with or without bone marrow aspirate, autograft or allograft (control group). After 5 weeks observation period, the authors reported similar effect on fixation of the implant by autograft and allograft while the hydroxyapatite/collagen composites, with or without bone marrow aspirate, did not have an effect on early fixation of the implants . In a later study by the same authors using the same animal model, the 2 mm gap was filled with demineralized bone matrix (DBM), DBM with cancellous bone at a ratio of 1:3, DME with allograft at a ratio of 1:3 or allograft (control group).…”
Section: Discussionmentioning
confidence: 91%
“…After 5 weeks observation period, the authors reported similar effect on fixation of the implant by autograft and allograft while the hydroxyapatite/collagen composites, with or without bone marrow aspirate, did not have an effect on early fixation of the implants. 39 In a later study by the same authors using the same animal model, 40 the 2 mm gap was filled with demineralized bone matrix (DBM), DBM with cancellous bone at a ratio of 1:3, DME with allograft at a ratio of 1:3 or allograft (control group). After 6 weeks observation period, results showed inferior early effects of DBM alone compared to the other groups on early fixation of the titanium implants.…”
Section: Clinical Relevancementioning
confidence: 99%
“…There are few studies in the literature that used pushout tests to evaluate the strength of the bone-implant interface in the calvaria, although this method is widely employed in other experimental bone surgery models, such as those of long bones of the limbs 22,23 . In an evaluation of the influence of growth hormone supplementation on calvarial healing using an identical protein-2 (BMP-2) after 15 weeks 25 , and of 138N using calcium deficient hydroxyapatite (CDHA) implants coated with chitosan and treated with BMP-2 after eight weeks 26 .…”
Section: Discussionmentioning
confidence: 99%